2021
DOI: 10.1016/j.celrep.2021.109841
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal domain of SARS-CoV-2 nsp1 plays key roles in suppression of cellular gene expression and preservation of viral gene expression

Abstract: Nonstructural protein 1 (nsp1) is a coronavirus (CoV) virulence factor that restricts cellular gene expression by inhibiting translation through blocking the mRNA entry channel of the 40S ribosomal subunit and by promoting mRNA degradation. We perform a detailed structure-guided mutational analysis of SARS-CoV-2 nsp1, revealing insight into how it coordinates these activities against host but not viral mRNA. We find that residues in the N-terminal and central regions of nsp1 not involved in docking into the 40… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
159
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(185 citation statements)
references
References 68 publications
25
159
1
Order By: Relevance
“…Additionally, Arg124 and Lys125 are not contacting to the ribosome in the model structure, which is consistent to the fact that the UV cross-linking to 18S RNA was unaffected by these two mutations. [15] On the other hand, recently reported Arg99Ala mutation to nsp1, which also lacks the ability to recognize viral RNA, [51] did not match important hydrogen bonds we found in the top clusters. This may be attributed to the insufficient sampling around Arg99 (it is not included in the REST2 region) and/or lack of important binding partners in the system, e.g.…”
Section: Relation To Other Experimental Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…Additionally, Arg124 and Lys125 are not contacting to the ribosome in the model structure, which is consistent to the fact that the UV cross-linking to 18S RNA was unaffected by these two mutations. [15] On the other hand, recently reported Arg99Ala mutation to nsp1, which also lacks the ability to recognize viral RNA, [51] did not match important hydrogen bonds we found in the top clusters. This may be attributed to the insufficient sampling around Arg99 (it is not included in the REST2 region) and/or lack of important binding partners in the system, e.g.…”
Section: Relation To Other Experimental Resultscontrasting
confidence: 75%
“…It has been reported that the Arg124Ala–Lys125Ala double nsp1 mutant lacks the ability to recognize viral RNA. [ 3 , 51 ] This can be explained by the results of our simulation, which showed that sidechain of Arg124 strongly interacts with the phosphate backbone of U18 ( Table 1 and Figs 4 and 9 ). An Arg124Ala mutation would eliminate the ionic interaction between the sidechain and the backbone, and nsp1 would lose its ability to recognize viral RNA.…”
Section: Resultsmentioning
confidence: 73%
“…The IFNL2-genomic and IFNL2-cDNA reporters were gifts from Dr. Marta Gaglia (Tufts University) [ 22 ]. The expression vectors for B2 SINEs and Adv-VAI were obtained from a prior study in the lab [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, Nsp1 C terminus binds to 40S ribosomal subunit and obstructs the mRNA entry tunnel, thereby, blocking antiviral responses triggered by RIG-I [145] . It was also suggested that SARS-CoV-2 Nsp1 prevents mRNA nuclear export through interaction with the host mRNA export receptor heterodimer NXF1-NXT1, which is involved in nuclear export of cellular mRNAs, thereby subsequently suppressing protein synthesis [146] , [147] .…”
Section: Immunoediting In Sars-cov-2mentioning
confidence: 99%